Bandido bom é bandido morto experiência estética e produção de sentidos nos programas policiais da televisão: o caso do Bandeira 2 - ALVES, Poliana Sales (2013)
This paper resulted from research on the police news on television that investigated the potential for communicability of this kind of programming from the aesthetic experience and the production of meanings derived from this experience. We seek to understand the sensitive dimension present in police news in terms of communicative processes / interactive set / designed by them. Therefore, our exercise will outline the specifics of aesthetic experience that can be performed on the interaction of viewers with the news police. The empirical reference of the research program was the Flag 2, aired 21 years ago on TV Difusora, police news oldest of Maranhão. By exploring murders, thefts, murders, police operations, lynching, this news is a program whose main attractions are content linked to violence, but always framed in the context of crime. We take for theoretical considerations of Dewey (1980), Jauss (1979), Iser (1999), Grumbrecht (2010) and Seel (1993).